2015
DOI: 10.2105/ajph.2015.302707
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trying Electronic Cigarettes on Cigarette Smoking by College Students: A Prospective Analysis

Abstract: Trying e-cigarettes during college did not deter cigarette smoking and may have contributed to continued smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 40 publications
6
77
1
2
Order By: Relevance
“…7,2124,3443 Point estimates in 13 of the 15 studies indicated decreased smoking cessation among those who used e-cigarettes, six of which reported statistically significant results. 24,34,36,40,41,43 One study 7 found that intensive e-cigarette users (those who used e-cigarettes daily for at least 1 month) had significantly increased smoking cessation and that intermittent e-cigarette users had a non-significant decrease in smoking cessation. In three studies without control groups (excluded from the meta-analysis), 16,45,46 smoking cessation rates among e-cigarette users ranged from 17% at 8 weeks, 45 to 41% at 1 year, 46 to 46% at 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…7,2124,3443 Point estimates in 13 of the 15 studies indicated decreased smoking cessation among those who used e-cigarettes, six of which reported statistically significant results. 24,34,36,40,41,43 One study 7 found that intensive e-cigarette users (those who used e-cigarettes daily for at least 1 month) had significantly increased smoking cessation and that intermittent e-cigarette users had a non-significant decrease in smoking cessation. In three studies without control groups (excluded from the meta-analysis), 16,45,46 smoking cessation rates among e-cigarette users ranged from 17% at 8 weeks, 45 to 41% at 1 year, 46 to 46% at 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 7% of respondents reported being current dual users of cigarettes and e-cigarettes in this sample. Other studies have also reported that current (last 30 day) and lifetime e-cigarette use now surpasses current and lifetime cigarette use (Johnston et al, 2016; Kenne et al, 2016; Ramo et al, 2015; Sutfin et al, 2015). Current college cigarette smokers are more likely to be current e-cigarette users than non-smokers and individuals who start using e-cigarettes, have a higher susceptibility and greater likelihood of becoming a cigarette smoker (Barrington-Trimis et al, 2016; Primack, Soneji, Stoolmiller, Fine, & Sargent, 2015; Sutfin et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…While device power is clearly important to understanding ECIG effects, many studies of ECIG users have not reported data regarding the power of the devices that those ECIG users use regularly (e.g., Vansickel and Eissenberg, 2013; Spindle et al, 2017; Spindle et al, 2017; Christensen et al, 2014; Brown et al, 2014; Hitchman et al, 2015; Sutfin et al, 2015). Of those that did, sample size was small (e.g., Wagener et al, 2017; N=20) or more than 50% of respondents did not know the power (wattage) of their device (Harvanko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%